Using Goals to Motivate College Students: Theory and Evidence From Field Experiments - Clark, Damon; Gill, David; Prowse, Victoria; Rush, Mark (The Review of Economics and Statistics, 2020)
Will college students who set goals work harder and perform better? We report two field experiments that involved four thousand college students. One experiment asked treated students to set goals for performance in the course; the other asked treated students to set goals for a particular task (completing online practice exams). Task-based goals had robust positive effects on the level of task completion and marginally significant positive effects on course performance. Performance-based goals had positive but small and statistically insignificant effects on course performance. A theoretical framework that builds on present bias and loss aversion helps to interpret our results.